Determinants of Generation Z Working in the Formal and Informal Sectors in West Nusa Tenggara - Luluk Fadliyanti; Wan Roshidah Binti Fadzim; Vici Handalusia Husni; Muhammad DzulFadlli (Universitas Negeri Malang, 2025)
This study aims to analyze the factors that influence Generation Z's decision to work in the formal and informal sectors in West Nusa Tenggara. This study adopts a descriptive quantitative approach. The population in this study consists of Generation Z individuals aged 15-26 years who work and have income, with a total population of 968 people. The data used in this study is secondary data from the August 2023 National Survey of the Labor Force (SAKERNAS), obtained from the Central Statistics Agency (BPS) of West Nusa Tenggara Province. The population is spread across ten districts/cities in West Nusa Tenggara Province. This study uses logit model analysis. The results showed that income and age had a negative and significant impact. In contrast, residence positively and considerably influenced the decision to work in the formal and informal sectors. Gender (female) also showed a negative and significant influence, while the duration of pre-employment education and training showed a negligible impact.